Doenças transmissíveis e situaç\~ao socioeconômica no Brasil: Análise espacial - Leila Posenato Garcia; Gabriela Drummond Marques da Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2016)
– Infectious diseases of poverty disproportionately affect people living in poor and marginalized communities. Poverty creates conditions that favor the spread of communicable diseases and prevents the affected people from obtaining adequate access to prevention and care. The use of social determinants as key analytical factors allows the identification of geographic aggregation patterns and spatial overlap of communicable diseases. This study objective is to describe the spatial distribution of epidemiological indicators of infectious diseases of poverty in Brazilian municipalities aiming to demarcate geographical areas of disease concentration and poor socioeconomic conditions for directing integrated public health and social policies. We conducted a descriptive ecological study with spatial approach, in which the Brazilian municipalities were the units of analysis. We used data from the information systems of the Brazilian Ministry of Health and the Brazilian Institute of Geography and Statistics to calculate incidence indicators of the following infectious diseases of poverty, according to their relevance to public health and availability of data: tuberculosis, leprosy, cutaneous leishmaniasis, visceral leishmaniasis and malaria. In the period 2009-2011 were reported in Brazil, 217,274 new cases of tuberculosis, 109,283 new cases of leprosy, 66,510 new cases of cutaneous leishmaniasis, 10,194 new cases of visceral leishmaniasis and, in the Legal Amazon region, 936,006 new cases of malaria. A large volume of these cases focused on a small portion of municipalities. Around 10% of Brazilian municipalities concentrated 80% of new cases of tuberculosis, leprosy and cutaneous leishmaniasis, diseases. For visceral leishmaniasis, 6% of municipalities concentrated 80% of new cases of the disease. Municipalities with the highest rates of urbanization had higher incidence of tuberculosis, while those with higher proportions of households with inadequate sanitation conditions had higher incidence of cutaneous and visceral leishmaniasis and leprosy also. Furthermore, the occurrence of these diseases was higher in the municipalities with higher poverty rate, higher inequality and more household crowding. The results of this study reinforce the persistence of various infectious diseases of poverty and its unequal distribution in the Brazilian territory. The study results emphasize the need of continuing investments and efforts to tackle these diseases, taking into account their pattern of spatial distribution, the geographical overlap between different diseases and between these and poor socioeconomic conditions, as well as other public policies that address the social determinants of health.
Keywords: I12; 330; communicable diseases; neglected diseases; health status indicators; social indicators; ecological studies